Pengaruh Hukum Islam Terhadap Pembentukan Hukum Nasional - Siti Amanah; Karina Tarigan, Eriza; Tamba, Taufik Hidayat; Azizah, Putri (Tabayyun : Journal Of Islamic Studies, 2025)
Islamic law has a significant role in the formation of national law in Indonesia, especially considering this country's status as a nation with the largest Muslim majority in the world. This article discusses how the principles of Islamic Law are integrated into the national legal system, both through legislation and recognition of customary law based on Islamic values. This research uses a normative juridical approach by examining statutory regulations, court decisions and other legal documents. The results of the study show that the contribution of Islamic law can be seen in various aspects, such as family law, sharia economic law, and sharia banking, as well as in the regulation of zakat and waqf. However, this integration still faces challenges, including the plurality of laws in Indonesia and the need to maintain the principles of diversity and justice for all citizens. This article recommends strengthening harmonization between the principles of Islamic law and universal principles in national law in order to create an inclusive and just legal system.